دور اللعب في التخفيف من السلوك العدواني لدى الطفل التوحدي دراسة لثلاث حالات من الأطفال بالمركز النفسي البيداغوجي للمعاقين ذهنيا رقم 2 ولاية الاغواط - حري منى; داودي محمد (My University, 2023)
The main objective of this study is to know the role of play in alleviating the aggressive behavior of the autistic child in the Psychological and Pedagogical Center for the Mentally Handicapped No. 2 in Laghouat City. You will focus on observing in-depth individuals with problems. The research group consisted of three cases of autistic children, whose ages ranged between 12 and 13 years, with moderate autism. The student applied two tools to collect study data: the observation network and the interview. The latter was based on two axes, the first being aggressive behavior and the second being play. After conducting the applied study, we reached the following conclusion: "To play an important role in alleviating the aggressive behavior of the autistic child.